RELATIONSHIP OF THE MINING SECTOR TO THE ELECTRICITY AND GAS PROCUREMENT SECTOR IN WEST PAPUA PROVINCE USING INPUT OUTPUT ANALYSIS: KETERKAITAN SEKTOR PERTAMBANGAN TERHADAP SEKTOR PENGADAAN LISTRIK DAN GAS DI PROPINSI PAPUA BARAT MENGGUNAKAN ANALISIS INPUT OUTPUT - Samudra Depari; Juanita R. Horman; Arif Setiawan (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2023)
Linkage analysis is a method used to understand the economic structure of a region. This analysis can also be used to figure out how much influence a sector has on other sectors based on the input and output tables for each sector. This research was conducted to analyze the forward and backward linkages of the mining and quarrying sector to the electricity and gas procurement sector in West Papua Province, both directly and indirectly. The data used in this research is sourced from the West Papua Province Input Output Table Domestic Transactions Based on Producer Prices 2016 Updated 2021. The method used in this research is a descriptive quantitative method. From the results of this research, it was found that the value of backward linkages in the mining and quarrying sector was more significant than the value of forward linkages, both directly and indirectly, to the electricity and gas procurement sector. Thus, the mining and quarrying sector requires more output from the electricity and gas procurement sector as input, compared to the electricity and gas procurement sector's need for the output of the mining and quarrying sector.